EXPLORING TEACHERS’ RESEARCH COMPETENCY: INPUTS TO POLICY ENHANCEMENT - Inero Ancho (ETERNAL (English, Teaching, Learning and Research Journal), 2019)
Using a convenience sample of 120 elementary, high school and senior high school classroom teachers in a City Schools Division, province of Bulacan, Philippines, the respondents were asked to complete a survey on general research skills and quantitative and qualitative research skills. The study explored the current status of teachers’ research competence. The results and findings of this study will serve as bases for policy enhancement. The policies anchored on concrete and evidence-based viewpoints contribute to successfully developing a culture of research among basic education teachers. As findings of the study reveal the current status of teacher-respondents regarding their research skills, overall numerical rating pegged to be “fair” when interpreted; it reflects a much serious state about their plight. The prerequisite to the successful implementation of research programs for teachers is on the basic assumption that teachers possess the necessary skills to do the task. Also, this is then being enhanced by revisiting teachers’ workload. Moreover, the presence of funding programs for teachers’ research projects exhibits a positive development in strengthening support for teachers’ professional development.